Modeling and Stability of Lotka-Volterra Prey-Predator System Involving Infectious Disease in Each Population - Naji, Raid; Ali, Nidhal (Iraqi Journal of Science, 2023)
In this paper, a mathematical model consisting of the prey- predator model with disease in both the population is proposed and analyzed. The existence, uniqueness and boundedness of the solution are discussed. The existences and the stability analysis of all possible equilibrium points are studied. Numerical simulation is carried out to investigate the global dynamical behavior of the system.